Peningkatan Literasi Gizi-Kesehatan Perempuan sebagai Upaya Pencegahan Malnutrisi pada Kelompok Rawan Gizi di Level Keluarga: Improving Women's Nutrition-Health Literacy as an Effort to Prevent Malnutrition on Vulnerable Groups at the Family Level - Sitti Patimah; Suchi Avnalurini Sharief; Nukman Nukman; Rezky Aulia Yusuf (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Currently, Indonesia is experiencing an emergency in nutritional-health problems, including Mangki Village, a village assisted by the Waqf Foundation of the Indonesian Muslim University. Women are the spearhead to preventing malnutrition and its consequences at the family level, which needs to be equipped with adequate nutrition-health knowledge. Therefore, service activities in the form of counseling are carried out to provide understanding to women about balanced nutrition, nutrition in nutritionally vulnerable groups, and nutrition-aware families. The method used in this service activity is a literacy approach with an extension model pre-post test to assess the effect of counseling from the Service Team. The results show that women's nutrition-health knowledge has increased by 19.4% significantly. Further efforts are needed to improve women's nutrition-health insight through community-based activities in Mangki Village such as PKK, Dasawisma, and Majelis Taklim by involving health workers and using simple educational media to be quickly understood by the women of Mangki village with low education.